An Analysis of the Cyber Security Opportunity and Challenges - Fatin Noori AL-HRAISHAW; Asst.Prof.Dr. Sefer Kurnaz (Scientific Trends, 2023)
Attempts to overload a system to the point where only a limited number of users are able to access a service are what are referred to as "denial of service" (DoS) or "distributed denial of service" (DDoS) attacks. Both terms refer to the same type of attack (DDoS). Hackers are able to take control of a large number of computers that have already been compromised as a result of the use of distributed denial of service (DDoS) attacks because these attacks can be launched against the standard architecture of the internet. The attacker will first select a target or targets, and then they will use a previously established attack network or botnet to coordinate a massive attack against those targets. The attacker may also select multiple targets at once. In light of the continuing growth in both the number of hosts that are susceptible to attack and the diversity of attack vectors, numerous strategies for detecting, preventing, and tracking distributed denial of service attacks have been proposed. These strategies aim to track down attacks, prevent attacks, and detect attacks. When conducting commercial monitoring of a system that is under attack from a DDoS, it is typical for a large number of packets to be involved in the process. They are to blame for significant delays on the network in addition to an exhaustion of its resources as a result of the fact that they infect thousands of hosts all at once. Attacks conducted via a network that uses distributed denial of service make it more difficult for us to take advantage of the infrastructure as a whole and its many benefits. Because of this, the authorized end users of the system will be shielded from any potential dangers that may arise. This article investigates the nature of distributed denial of service attacks, also known as DDoS attacks, as well as the methods that are used to launch them and the countermeasures that can be put into place to defend against them. In this paper, we investigate a number of different strategies for detecting distributed denial-of-service attacks, defending against them, and mitigating their effects.
Keywords: DDOS , Defense , Denial of services.